Evaluation of Efficacy in a Pancreas and Pancreas–Kidney Pretransplantation Orientation Group - Simon Guimaro, M.; Silva Lacerda, S.; Aparecida Yamada Yonezawa, E.; Hegedus Karam, C.; Roberto de Sá, J.; Perosa de Miranda, M.; Bruno de Araújo Andreoli, P. (Transplantation proceedings, 2007)
There is evidence of benefits from psycho-educational groups in the compliance of patients undergoing complex procedures. Psycho-educational groups provide information, elucide doubts and realities, fade out fantasies, and help lessen patients’ anxieties, thus minimizing the chances of complications or irregular behavior. The objective of this study was to evaluate the efficacy of an interdisciplinary orientation group for pretransplantation preparation for pancreas/pancreas–kidney grafting. All patients and their accompanying persons who attended information groups from February to August 2005 completed a questionnaire with 15 relevant items about the transplantation process. The efficiency of the orientation group was evaluated according to the percentage of correct answers before and after attending the group. Twenty-seven subjects were evaluated demonstrating an increased number of right answers in 78% of the evaluated items after group attendance. An important improvement was observed in the following items: function of serum sent to the Central Laboratory; serum replacement period; kind of renal donor; blood transfusion; using medicaments; and how often should the patient return for an appointment with the surgeon within the first month. Further items such as surgery risks, using immunosuppressive drugs, and forgetting the medication showed 100% correct answers before and after attending the group. Results suggest that the pretransplantation orientation group is an efficient way to provide information. Applying a knowledge verification questionnaire before and after the group helps to understand the difficulties of participants, thereby guiding the team and elucidating questions that need more consideration.